Policy Content Analysis of Population Administration Online Service Policies during the Pandemic in Yogyakarta: A Logical Framework Review - Martino, Martino (Jurnal Borneo Administrator, 2024)
The pandemic has presented unprecedented challenges to public administration by disrupting fundamental public services. The government is responsible for managing public interests and responding effectively to crises. Inadequate crisis response can lead to a collapse in essential public services, including population administration services. Studies on the policy cycle during a crisis are still relatively limited. After the COVID-19 crisis prompted efforts to investigate and document policy developments during the situation, the significance of this study has increased. This study examined the policy process of population administration online services in Yogyakarta during the pandemic, particularly by analyzing policy content perspectives. This study analyzed policy input, process, output, and impacts using a qualitative case study methodology in a logical framework approach. The findings indicate that the political system effectively adapts to the policy environment, converting inputs into policy adoption and producing coherent policy outputs. The use of online systems aims to ensure vital government services continue without interruption while minimizing risks. This adaptation improves accessibility and efficiency, ensuring valid population documentation, data integrity, and legal certainty. Rather than formulating new policies, policy adoption is made through learning, negotiation, and swift dissemination across government levels. However, individuals lacking access to technology or digital literacy skills face exclusion risks. Addressing ongoing online service changes post-pandemic is crucial for efficiency. The policy process highlights agility, innovation, and collaboration in managing crises and delivering public services effectively. Leveraging technology and adaptive governance enhances public governance resilience and capacity to meet community needs